2020
DOI: 10.1016/j.redox.2020.101687
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the post-genomic era: Globin diversity beyond oxygen binding and transport

Abstract: Vertebrate hemoglobin (Hb) and myoglobin (Mb) were among the first proteins whose structures and sequences were determined over 50 years ago. In the subsequent pregenomic period, numerous related proteins came to light in plants, invertebrates and bacteria, that shared the myoglobin fold, a signature sequence motif characteristic of a 3-on-3 α-helical sandwich. Concomitantly, eukaryote and bacterial globins with a truncated 2-on-2 α-helical fold were discovered. Genomic information over the last 20 years has d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 312 publications
(435 reference statements)
2
47
0
Order By: Relevance
“…Genomic analyses have considerably altered and extended our view of the globin family in mammals, leading to the discovery of novel globin types such as neuroglobin (NGB) and cytoglobin (CYGB), which are expressed in nerve and fibroblast-like cells, respectively ( 1 , 2 ). Both globin types perform yet-to-be-illuminated functions, which possibly reside in antioxidant defense, reactive oxygen species signaling, or even lipid metabolism ( 3 , 4 ).…”
mentioning
confidence: 99%
“…Genomic analyses have considerably altered and extended our view of the globin family in mammals, leading to the discovery of novel globin types such as neuroglobin (NGB) and cytoglobin (CYGB), which are expressed in nerve and fibroblast-like cells, respectively ( 1 , 2 ). Both globin types perform yet-to-be-illuminated functions, which possibly reside in antioxidant defense, reactive oxygen species signaling, or even lipid metabolism ( 3 , 4 ).…”
mentioning
confidence: 99%
“…Since the time of its initial discovery (Roesner et al, 2005), GbX went from being an obscure gene found in a very limited sample of vertebrates to becoming a credible candidate to provide clues about the functional role of the ancestor of all animal globins (Blank et al, 2011; Song et al, 2020). This change in paradigm came with an increased interest in deciphering its evolutionary history and its still elusive functional role (Burmester and Hankeln, 2014; Keppner et al, 2020). We have recently documented the presence of GbX paralogs in arthropods (Prothmann et al, 2020), confirming phylogenetic predictions that indicate that the origin of GbX predates the split between deuterostomes and protostomes (Burmester et al, 2002; Roesner et al, 2005; Dröge and Makałowski, 2011; Blank and Burmester, 2012; Hoffmann et al, 2012a)(Opazo et al, 2015), which is estimated to have occurred ~ 730 million years ago (Kumar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Globins are small, oxygen-binding hemoproteins found in all domains of life (Vinogradov et al, 2005). The globin superfamily of vertebrates provides an excellent example of how the interplay between local gene duplications, whole-genome duplications, amino acid and regulatory changes can fuel the evolution of novel protein functions (Storz et al, 2011, 2013; Keppner et al, 2020). The different types of globins in vertebrate genomes can be classified into four groups 1)-androglobin, 2)-neuroglobin,3) globin-X (GbX), and 4)-vertebrate-specific globins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globins are small globular metallo-proteins, which have the capacity to reversibly bind gaseous ligands via a typical 8 alpha-helical structure in which a heme prosthetic group can be embedded. In mammals, five globin types exist: the well-established hemoglobin (Hb) and myoglobin (Mb), neuroglobin (Ngb) in neuronal cells, cytoglobin (Cygb) ubiquitously expressed in fibroblasts, and the more recently identified androglobin (Adgb), predominantly expressed in mammalian testis tissue (Keppner et al 2020).…”
Section: Introductionmentioning
confidence: 99%